Аналіз методології оцінки економічних показників відновлення авіаційної техніки - Калиновський, А. О.; Калиновська, Н. Л.; Гулько, О. С.; Онищенко, І. Р.; Kalynovskyi, A. O.; Kalynovska, N. L.; Hulko, O. S.; Onishchenko, I. R. (Видавництво Львівської політехніки, 2023)
Представлена наукова стаття присвячена вивченню проблем оцінки якості технічного обслуговування і відновлення авіаційної техніки. В ній розглянуто різні методики оцінки з урахуванням їх переваг і недоліків, а також висвітлено важливість врахування економічних наслідків при оцінці якості обслуговування авіаційної техніки. Зроблено акцент на аналізі поточних підходів та перспектив подальших досліджень у цій галузі, охоплюючи розробку універсальних методик, використання новітніх технологій та створення стандартів оцінки. Відзначено значущість врахування широкого спектра факторів для забезпечення комплексного підходу до оцінки якості технічного обслуговування авіаційної техніки.

The article delves into the complexities of evaluating the economic aspects of maintaining and restoring aviation equipment, highlighting the challenges associated with assessing the quality of these processes. It critically examines the use of both singular and multiple performance metrics, emphasizing the need for a comprehensive evaluation system that considers various industry-specific factors. Drawing from methodologies utilized in the chemical and shipbuilding sectors, the study underscores the significance of incorporating diverse parameters, including equipment complexity, labor costs, and technical infrastructure, in the evaluation framework. The article investigates the methodologies for assessing the quality of technical maintenance and restoration of aviation equipment, focusing on the complexities associated with evaluating economic indicators. It discusses the limitations of using singular versus multiple performance metrics in assessing the effectiveness of maintenance processes. Furthermore, the article emphasizes the significance of not only quantifying the costs but also analyzing the economic outcomes in relation to the operational efficiency of the aviation fleet. It underlines the necessity of establishing a direct correlation between the incurred expenses and the resultant operational status of the aviation equipment. In light of the research findings, the article advocates for the implementation of a holistic approach that integrates both quantitative expenditure analysis and qualitative assessments of the fleet’s functional state. The study concludes by proposing a sequential research framework for investigating the economic dimensions of aviation equipment maintenance, emphasizing the interconnected nature of maintenance quality, operational status, and equipment utilization efficiency. It calls for further exploration of these interconnected factors to develop a more nuanced understanding of the economic dynamics within the realm of aviation equipment maintenance.
Analysis of the methodology for estimating the economic indicators of aviation equipment restoration
Keywords: оцінка якості; технічне обслуговування; відновлення; авіаційна техніка; економічна ефективність; quality assessment; maintenance; restoration; aviation technology; economic efficiency; 629.73.083; 338.47-044.3(477)